Design of efficient electrocatalysts for hydrogen evolution reaction based on 2D MXenes - Wei, Yi; Soomro, Razium A.; Xie, Xiuqiang; Xu, Bin (Journal of energy chemistry, 2021)
This review focuses on the recent progresses, mechanisms of action and regulation directions on MXenes-based electrocatalysts in HER including pristine MXenes and MXenes-based composites. [Display omitted] The growing energy concern all over the world has recognized hydrogen energy as the most promising renewable energy sources. Recently, electrocatalytic hydrogen evolution reaction (HER) by water splitting has been extensively studied with a focus on developing efficient electrocatalysts that can afford HER at overpotential with minimum power consumption. The two-dimensional transition metal carbides and nitride, also known as MXenes, are becoming the rising star in developing efficient electrocatalysts for HER, owing to their integrated chemical and electronic properties, e.g., metallic conductivity, variety of redox-active transition metals, high hydrophilicity, and tunable surface functionalities. In this review, the recent progress about the fundamental understanding and materials engineering of MXenes-based electrocatalysts is summarized in concern with two aspects: i) the regulation of the intrinsic properties of MXenes, which include the composition, surface functionality, and defects; and ii) MXenes-based composites for HER process. In the end, we summarize the present challenges concerning the efficiency of MXenes-based HER electrocatalysts and propose the directions of future research efforts.